Accidental Prepubic Tendon ,Rupture and Fetal Mummification in a Goat - SINGH, BHOOPENDRA; GANGWAR, A K; SINGH, S V; SINGH, J P; SINGH, H N (The Indian Journal of Animal Reproduction, 2023)
A rare case of accidental prepubic tendon rupture with fetal mummification in goat and its treatment by caesarean operation is reported in this communication.